FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEMAMPUAN KELUARGA DALAM PENCEGAHAN KEKAMBUHAN PASIEN SKIZOFRENIA : Factors Associated with Family Ability in Prevention of Recurrence of Schizophrenic Patients - Suhardiana Rachmawati; Ahmad Yusuf; Rizky Fitriyasari (LPPM STIKES Pemkab Jombang, 2020)
One problem in treating schizophrenia is recurrence. Recurrence indicates the return of symptoms of the previous disease is quite severe and disturbing daily activities and requires further treatment. Prevention of recurrence in schizophrenia can be sought by the family. This study aims to identify factors related to family abilities in preventing recurrence of schizophrenic patients. This study used a cross sectional design. The sample in the study were 82 families with family members of schizophrenic patients obtained using simple random sampling. The results of the analysis have a relationship between the age range of the family (p value 0.012), the role of respondents in the family (p value 0.032), duration of treating schizophrenic patients (p value 0.001) but there is no relationship between the ability to prevent recurrence with the sex of respondents (p value 0.835) and education level of respondents (p value 0.508). Recommendations from this study for health workers provide health education to families to provide an understanding of the ability to prevent recurrence in schizophrenic patients. Keywords: Schizophrenia, Prevention of recurrence, Family